2013
DOI: 10.1007/s00246-013-0843-9
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Supine and Upright Blood Pressure Associates to the Efficacy of Midodrine on Postural Orthostatic Tachycardia Syndrome (POTS) in Children

Abstract: Postural orthostatic tachycardia syndrome (POTS) is common, and has a serious impact on children's quality of life. Midodrine hydrochloride, an α1-adrenoreceptor agonist, is an effective treatment. The study was designed to examine the therapeutic efficacy of midodrine hydrochloride by quantifying changes in blood pressure during the head-up test (HUT), in children with POTS. Overall, 104 out of 110 children with POTS were treated with midodrine hydrochloride and successfully followed-up. Systolic blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Midodrine hydrochloride is effective for some forms of pediatric POTS [46][47][48][49][50][51]. The initial dose usually is 2.5 mg once or twice a day, with an increase to 2.5 mg three times a day, as necessary [46][47][48][49][50][51]. BP should be monitored during the treatment.…”
Section: Midodrine Hydrochloridementioning
confidence: 99%
See 1 more Smart Citation
“…Midodrine hydrochloride is effective for some forms of pediatric POTS [46][47][48][49][50][51]. The initial dose usually is 2.5 mg once or twice a day, with an increase to 2.5 mg three times a day, as necessary [46][47][48][49][50][51]. BP should be monitored during the treatment.…”
Section: Midodrine Hydrochloridementioning
confidence: 99%
“…Hemodynamic indexes and biomarkers are useful for drug selection. Midodrine hydrochloride is indicated with flow-mediated dilation >9.85% [49], hydrogen sulfide production from erythrocytes >27.1 nmol/min [50], plasma midregional proadrenomedullin level >61.5 pg/mL [51], plasma copeptin level >10.5 pmol/L [46], pre-treatment increase of SBP 0 mmHg, or pre-treatment increase of DBP 6.5 mmHg (from the supine position to standing) [47] but with BP greater than the 95th percentile BP value by age and sex or with drug allergy (IIa; B).…”
Section: Midodrine Hydrochloridementioning
confidence: 99%
“…To find out a simple and noninvasive method to select the responders to the midodrine treatment, Deng et al . [ 33 ] tried to analyze the usefulness of blood pressure change from supine to upright before treatment to predict the effectiveness of midodrine on POTS in children. They found that children with POTS would respond well to midodrine when the pretreatment increase of systolic blood pressure was ≤0 mmHg (1mmHg=0.133kPa), or when the pretreatment increase of diastolic blood pressure was ≤6.5 mmHg (from the supine position to upright), with a sensitivity of 72% and specificity of 88%.…”
Section: T He I Ndividualized Tmentioning
confidence: 99%
“…In 2013, Deng et al found that midodrine hydrochloride for children with postural tachycardia syndrome would be predicted to be effective when the pre-treatment increase in systolic blood pressure was ⩽0 mmHg, or when the pre-treatment increase in diastolic blood pressure was ⩽6.5 mmHgfrom the supine position to standingyielding a sensitivity of 72% and specificity of 88%. 38 Haemodynamic change during head-up tilt test as a predictor for the therapeutic response to β-adrenoceptor blocker in children with vasovagal syncope…”
Section: Treatment Status Of Postural Tachycardia Syndrome and Vasovamentioning
confidence: 99%